Knowledge Improvement on Burn Injury Prevention and First Management after One-Day Health Promotion Event (Majalah Kedokteran Bandung, 2019)
Burns causes a significant number of mortality and morbidity globally with a higher number found in developing countries, such as Indonesia. A study conducted in Indonesia discovered that the majority of burns were caused by flame LPG-related (liquefied petroleum gas) burns (33%), which is understandable because LPG is the main cooking fuel used in Indonesian homes. Since the first management of burn will influence the outcome of burn injuries, health promotion efforts to improve knowledge, attitude, and practice to prevent burns and to provide first aid for burn are considered important to reduce burn-related morbidity and mortality. This was a descriptive study conducted in Babakan Sari Sub-district, Antapani, Bandung, Indonesia which involved a one-day community health promotion event as the intervention. The aim of this study was to compare the level of knowledge regarding burn prevention and first management before and after a one-day community health promotion event. As many as 61 respondents were recruited through purposive sampling and these respondents were asked to fill out a pre-event questionnaire consisting of questions regarding demographic data and knowledge on burn prevention and management. Demographic data collected showed that 31% of participants had experienced burns; 100% of participants used 3kg LPG gas tank in their home; 98% of participants had never been taught on how to handle an emergency situation or how to arrange an evacuation route; and 100% of participants felt that their neighborhood did not provide facilities for burn management. A post-event questionnaire was distributed after the one-day health promotion event, which was conducted in October 2018, and the results were compared with the pre-event questionnaire results. A significant improvement of knowledge was seen, as evident from the increase of a median score from 2.0 before the event to 9.0 after the event (p
Keywords: Burns; Community Health Services; Health Promotion; Public Health